Oral–Maxillofacial Injury Surveillance of U.S. Military Personnel in Iraq and Afghanistan, 2001 to 2014. Issue 3 (1st March 2017) - Mitchener, Timothy A.; Chan, Rodney; Simecek, John W.
ABSTRACT: Background: Cranial and oral–maxillofacial injuries accounted for 33% of military visits to in-theater (Level III) military treatment facilities for battle injuries during Operation Enduring Freedom (OEF) and Operation Iraqi Freedom (OIF). Even after years of conflict, the size and scope of oral–maxillofacial injuries in military armed conflict is still not fully understood. This study reports U.S. Department of Defense (DoD) rates of oral–maxillofacial injuries that can be used for further surveillance and research. Methods: The populations studied were military personnel deployed to Afghanistan in OEF or Iraq in OIF and Operation New Dawn (OND), who sought care at a Level III military treatment facility for one or more oral–maxillofacial injuries. Injuries were identified in the DoD Trauma Registry (DoDTR) using diagnosis codes associated with oral–maxillofacial battle and nonbattle injuries. All oral–maxillofacial injuries incurred from October 19, 2001, to June 30, 2014, were included. The Defense Manpower Data Center provided DoD troop strength numbers to serve as the study denominators. Results: Battle injuries accounted for 80% of oral–maxillofacial injuries in OEF. There were 2, 504 oral–maxillofacial injuries in OEF. The Army accounted for 1, 820 (72.7%), the Marines 535 (21.3%), the Air Force 75 (3.0%), and the Navy 74 (3.0%). The oral–maxillofacial injury rates in OEF for the Army ranged from 1.10 to 4.90/1, 000 person years (PY), for the Marines from 0.57 to 9.39/1, 000 PY, for the Navy from 0 to 3.29/1, 000 PY, and for the Air Force from 0 to 3.38/1, 000 PY. The Army tended to have the highest incidence of all services in the early and latter part of the conflict, whereas Marines tended to have the highest incidence in the middle years. The Marines, Army, and Navy all had their individual highest incidences in 2009, the first year of the 2009 to 2011 OEF troop surge. Battle injuries accounted for 75% of oral–maxillofacial injuries in OIF/OND. There were 3, 676 oral–maxillofacial injuries in OIF/OND. The Army accounted for 2, 798 (76.1%), the Marines 731 (19.9%), the Navy 91 (2.5%), and the Air Force 56 (1.5%). The injury rates in OIF/OND for the Army ranged from 0.66 to 8.69/1, 000 PY, for the Marines from 0.88 to 42.7/1, 000 PY, for the Navy from 0.35 to 19.16/1, 000 PY, and for the Air Force from 0.24 to 1.13/1, 000 PY. In OIF/OND, the Marines had the highest overall oral–maxillofacial injury rate (42.70/1, 000 PY) in 2003. The other services had their individual peak incidences in either 2003 or 2004. Discussion/Impact/Recommendations: This is the first study, which quantified the incidence of oral–maxillofacial injury in theaters of conflict over prolonged periods. The Army has the highest number of injuries. The Marines had the highest incidences during the initial stages of OIF and the OEF troop surge. Intensity of the conflict could account for the upswing in rates. These increases in injury rates highlight the need for additional health care personnel to be deployed near the battlefield to treat these injuries.